Analysis of paper foxing by newly available omics techniques. (August 2018) - Szulc, Justyna; Otlewska, Anna; Ruman, Tomasz; Kubiak, Katarzyna; Karbowska-Berent, Joanna; Kozielec, Tomasz; Gutarowska, Beata
Abstract: The aim of this study was to determine the cause of foxing on 19th century paper using omics methods, including metagenomics via high-throughput sequencing on the Illumina platform and metabolomics via high-resolution surface-assisted laser desorption/ionization time-of-flight mass spectrometry (SALDI-ToF-MS) imaging using the gold nanoparticle-enhanced target (AuNPET) method. Metabolomic analysis as well as ninhydrin and amido black staining of paper samples showed the presence of proteinaceous substances in areas corresponding to foxing. Products of cellulose biodegradation and microbial metabolites, including yellow-coloured pigments (2-methyl-6-phytylquinol; delta-, gamma- and beta-tocopherols; 3-hydroxy-L-kynurenine) were detected. No difference in metal-ion content was seen between areas with and without foxing. Higher degrees of biodiversity were identified within foxing stains compared to foxing-free areas. Phoma sp. and Cladonia sp. moulds and Gluconobacter and Ralstonia bacteria were predominant in DNA samples obtained from foxing stains. The presence of these microbes has never previously been linked to the phenomenon of foxing. These studies indicate that foxing is a result of a combined effect of microbial action, paper-degradation by microbes, dye production, and chemical changes occurring in paper due to oxidation of cellulose metabolites. Highlights: Omics methods are useful tool for foxing diagnostics. Higher biodiversity was identified in foxing regions compared to control paper areas. Compounds from cellulose degradation and microbial activity were in foxing regions. Foxing is a result of microorganisms action and chemical changes in paper.